PENDIDIKAN AGAMA ISLAM MODERAT DI PESANTREN: STUDI KASUS PROSES PEMBELAJARAN DI PESANTREN AL-FATH CILEGON - M. Muizzuddin; Muhammad Alamul Huda (MIYAH : Jurnal Studi Islam, 2024)
Abstract: Al-Fath Cilegon Islamic Boarding School is one of the institutions that strives to maintain the values of Islamic teachings according to Ahlus Sunnah wal Jamaah by integrating moderate Islamic values into all forms of activities and daily life at the pesantren. It is hoped that the alumni can become young men and women who can uphold the Aqidah of Ahlus Sunnah wal Jamaah. The method used is qualitative with a case study approach. To obtain valid data, the researcher uses primary data (interviews, observations) and secondary data (documentation, data analysis, and data verification). The results of the study indicate that there are three stages in the process of learning moderate Islamic education at Al-Fath pesantren: 1) the planning stage, which includes the establishment of syllabi, programs, and schedules; 2) the implementation stage, which includes core activities, extracurricular activities, and incidental activities; and 3) the evaluation stage, which refers to three aspects of assessment: cognitive, affective, and psychomotor, with forms of reward or punishment. Keywords: Moderate Islam, Ahlus Sunnah wal Jamaah, Rahmatan lil Alamin, Islamic Boarding School.